(Dis)embeddedness and (de)commodification: COVID-19, Uber, and the unravelling logics of the gig economy. Issue 2 (July 2020) - Katta, Srujana; Badger, Adam; Graham, Mark; Howson, Kelle; Ustek-Spilda, Funda; Bertolini, Alessio
The ride-hailing giant Uber has long circumvented labour regulations and commodified its drivers' labour by existing at the conjuncture of multiple geographies – being simultaneously embedded and disembedded from the places where it operates. In this commentary, we argue that the COVID-19 pandemic has destabilised Uber's 'conjunctural' existence and forced the company to become more embedded in the locations where it operates, bringing about a – perhaps temporary – turn towards the decommodification of its drivers' labour.